Determinants of bird conservation‐action implementation and associated population trends of threatened species. Issue 6 (24th August 2016) - Luther, David A.; Brooks, Thomas M.; Butchart, Stuart H.M.; Hayward, Matt W.; Kester, Marieke E.; Lamoreux, John; Upgren, Amy
Abstract: Conservation actions, such as habitat protection, attempt to halt the loss of threatened species and help their populations recover. The efficiency and the effectiveness of actions have been examined individually. However, conservation actions generally occur simultaneously, so the full suite of implemented conservation actions should be assessed. We used the conservation actions underway for all threatened and near‐threatened birds of the world (International Union for Conservation of Nature Red List of Threatened Species) to assess which biological (related to taxonomy and ecology) and anthropogenic (related to geoeconomics) factors were associated with the implementation of different classes of conservation actions. We also assessed which conservation actions were associated with population increases in the species targeted. Extinction‐risk category was the strongest single predictor of the type of conservation actions implemented, followed by landmass type (continent, oceanic island, etc.) and generation length. Species targeted by invasive nonnative species control or eradication programs, ex situ conservation, international legislation, reintroduction, or education, and awareness‐raising activities were more likely to have increasing populations. These results illustrate the importance of developing a predictive science of conservation actions and the relative benefits of each class of implemented conservation action for threatened and near‐threatened birds worldwide.